2019
DOI: 10.1021/acs.analchem.8b04928
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Pure Shift HSQC NMR for Untargeted Metabolomics

Abstract: Sensitivity and resolution are key considerations for NMR applications in general, and for metabolomics in particular, where complex mixtures containing hundreds of metabolites over a large range of concentrations are commonly encountered. There is a strong demand for advanced methods that can provide maximal information in the shortest possible time frame. Here we present the optimization and application of the recently introduced 2D real-time BIRD 1 H-13 C HSQC experiment for NMR-based metabolomics at 13 C n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 76 publications
0
28
0
Order By: Relevance
“…A newer approach, called pure-shift NMR spectroscopy [233,234,235,236,237,238], has emerged and achieves even better decoupling and even greater spectral simplification. Indeed, pure-shift NMR promises significant benefits for the analysis of complex mixtures through improvements in both resolution and sensitivity [239,240].…”
Section: New Nmr Methods In Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A newer approach, called pure-shift NMR spectroscopy [233,234,235,236,237,238], has emerged and achieves even better decoupling and even greater spectral simplification. Indeed, pure-shift NMR promises significant benefits for the analysis of complex mixtures through improvements in both resolution and sensitivity [239,240].…”
Section: New Nmr Methods In Metabolomicsmentioning
confidence: 99%
“…For example, the real-time BIRD (bilinear rotation decoupled) HSQC, proposed by Paudel et al, achieves improved spectral resolution without sacrificing sensitivity [244]. Most recently, a real-time pure shift HSQC-SI sequence optimized for metabolomics studies has been shown to have a ~40% to 50% sensitivity enhancement over conventional pure-shift NMR experiments [240]. As a result, efforts to apply pure-shift NMR methods to metabolomics studies are now underway [240,247,248].…”
Section: New Nmr Methods In Metabolomicsmentioning
confidence: 99%
“…Such a pure-shift 2D HSQC approach was in fact included in the QUIPU approach, already mentioned in the previous section, which was successfully applied to various targeted quantitative studies. 19,51,65 In 2019, Timári et al suggested that the pure-shift 2D approach could be relevant for untargeted metabolomics; 66 application to a real untargeted metabolomics study could be expected in the near future. Finally, the first application of pure-shift NMR to the field of fluxomics has been reported very recently by Sinnaeve et al, who developed a pure-shift 2D…”
Section: Pure-shift Nmrmentioning
confidence: 99%
“…The inclusion of typical conditions like developed kit, software for pulse sequence design and high‐field apparatus has improved the efficiency of metabolite identification by HSQC‐NMR study (Timari et al . 2019). Chemical shift values and proton assignments for milk metabolites identified by 1 H NMR spectroscopy are presented in Table 1.…”
Section: Analytical Techniques In Milk Metabolomicsmentioning
confidence: 99%